10=12-2z

Simple and best practice solution for 10=12-2z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10=12-2z equation:


Simplifying
10 = 12 + -2z

Solving
10 = 12 + -2z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '2z' to each side of the equation.
10 + 2z = 12 + -2z + 2z

Combine like terms: -2z + 2z = 0
10 + 2z = 12 + 0
10 + 2z = 12

Add '-10' to each side of the equation.
10 + -10 + 2z = 12 + -10

Combine like terms: 10 + -10 = 0
0 + 2z = 12 + -10
2z = 12 + -10

Combine like terms: 12 + -10 = 2
2z = 2

Divide each side by '2'.
z = 1

Simplifying
z = 1

See similar equations:

| 0.01x+0.10(100-x)=0.41x | | 12=2(5x+6) | | 10y=2x+3zy+1 | | -5r-7=8 | | -(8x-2)=-(2x-2) | | 2y+3y-18=-83 | | 1=z+3 | | 2(lnx)*2-9lnx-18=0 | | 40+4x=28 | | 5+15=25 | | -3(8n-3)=-33-4n | | 2z-1=2z-5 | | 2(1+8x)=-110 | | 2x+40=0.18 | | -0.10(41)+0.85x=0.05(x-18) | | -4(8+4x)-8=-40-8x | | -(7x-3)+4x-5=-2 | | 4(3x+2)-x=x | | 6(3+w)+3w+5(4w+2)= | | 0=2205C-(1+C^2)(4.9)(2.48)-183 | | 4(3x+2)-x=x+1 | | 3x+25=3+7x-6 | | 5p=2p+4 | | 10=12-22 | | 4(3x+2)-x=x-3 | | 3p-2=-7 | | -0.2k+2.8k=0.48 | | p-7=-5(-3p-7) | | 2(x+7)-12= | | 0.15y+0.04(y+6000)=1000 | | 4K^2+21K+72= | | 5+(x-5)+(x-4)=16+10+(x+10) |

Equations solver categories